2018
DOI: 10.1016/j.omtn.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Targeting of Granulin in Hepatoma Cells by Synthetic CRISPR dCas9 Epi-suppressors

Abstract: The CRISPR-associated Cas9 system can modulate disease-causing alleles both in vivo and ex vivo, raising the possibility of therapeutic genome editing. In addition to gene targeting, epigenetic modulation by the catalytically inactive dCas9 may also be a potential form of cancer therapy. Granulin (GRN), a potent pluripotent mitogen and growth factor that promotes cancer progression by maintaining self-renewal of hepatic stem cancer cells, is upregulated in hepatoma tissues and is associated with decreased tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 55 publications
(61 reference statements)
0
31
0
Order By: Relevance
“… 30 , 31 , 32 By tethering the C terminus of the catalytically inactive dCas9 to three epigenetic suppressor domains, we found that the synthetic dCas9 epi-suppressor gRNAs induced significant decreases in the transcription activity of the GRN target gene promoter in Hep3B hepatoma cells. 33 In this study, we have successfully applied the Cas9 system to introduce a powerful promoter in front of the IRAIN lncRNA. The Cas9-mediated ALIC approach leads to an increase in IRAIN antisense lncRNA, which induces the downregulation of the sense IGF1R coding RNA through the cis transcription competition over the overlapping promoter.…”
Section: Discussionmentioning
confidence: 99%
“… 30 , 31 , 32 By tethering the C terminus of the catalytically inactive dCas9 to three epigenetic suppressor domains, we found that the synthetic dCas9 epi-suppressor gRNAs induced significant decreases in the transcription activity of the GRN target gene promoter in Hep3B hepatoma cells. 33 In this study, we have successfully applied the Cas9 system to introduce a powerful promoter in front of the IRAIN lncRNA. The Cas9-mediated ALIC approach leads to an increase in IRAIN antisense lncRNA, which induces the downregulation of the sense IGF1R coding RNA through the cis transcription competition over the overlapping promoter.…”
Section: Discussionmentioning
confidence: 99%
“…ChIP assay was used to examine the binding of TET1 to the FLI1 promoter and was performed using the method as described previously [50]. In brief, FECR1-overexpressing and vector control cells were fixed with 1% formaldehyde, sonicated on ice for 180 s (10 s on and 10 s off), and immunoprecipitated with an anti-TET1 antibody (Invitrogen, CA).…”
Section: Methodsmentioning
confidence: 99%
“…The group then designed gRNAs specific to the GRN promoter. Epigenetic targeting of GRN decreased tumor cell growth compared with the random gRNA control and dCas9 control groups ( 36 38 ), thus introducing a powerful epigenetic tool for oncogenes’ inhibition.…”
Section: Crispr/cas and Tumor Cell Manipulationmentioning
confidence: 97%
“…Recently, the CRISPR/Cas9 system has shed light on the underlying epigenetic irregularities and rendered researchers able to target these irregularities using the CRISPR/Cas9 platform. Wang et al (36) targeted granulin (GRN), a liver cancer stem cell marker, epigenetically using the CRISPR/Cas9 system. The system consisted of C-terminus of the catalytically inactive dCas9 fused to three epigenetic suppressor domains: DNMT3a, histone 3 K27 methyltransferase EZH2, and heterochromatin binding suppressor KRAB.…”
Section: Gene Therapy Via Crispr/casmentioning
confidence: 99%